The novel KIR2DL1 allele, KIR2DL1*037, defined in the cell line SPO010 (IHW9036). (June 2018) - Bultitude, W. P.; Gymer, A. W.; Robinson, J.; Mayor, N. P.; Marsh, S. G. E.
Abstract : The novel KIR2DL1*037 allele discovered and characterised by single molecule real‐time (SMRT) DNA sequencing.